2010
DOI: 10.1097/mat.0b013e3181e6bf13
|View full text |Cite
|
Sign up to set email alerts
|

Prediction Value of Model for End-Stage Liver Disease Scoring System on Prognosis in the Acute on Chronic Liver Failure Patients With Plasma Exchange Treatment

Abstract: Hepatitis B virus-related acute-on-chronic liver failure (AoCLF) is associated with a high mortality rate. Plasma exchange (PE) is useful to bridge patients with AoCLF to liver transplantation or recovery. The aim of this study was to analyze the impact of the model for end-stage liver disease (MELD) score on 30-day survival in patients with AoCLF treated with PE or conventional medications and to evaluate the therapeutic effectiveness of PE. In this study, 62 enrolled patients with AoCLF who received PE treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
55
0
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 54 publications
(66 citation statements)
references
References 11 publications
5
55
0
6
Order By: Relevance
“…The MELD score is a prospectively developed and validated scale for the severity of end-stage liver disease that uses the quantitative, objective values of serum TBIL, serum creatinine, and INR of prothrombin time to predict patient mortality in patients with advanced liver disease [16,40]. Mao et al’s study reported that the MELD score was related to the prognosis of patients with HBV-related acute-on-chronic liver failure [41]. We found that although the AUC of PAF-AH was lower than the AUC of the MELD score for predicting CSHB, the AUC of PAF-AH combined with MELD score was higher than that of PAF-AH or the MELD score alone.…”
Section: Discussionmentioning
confidence: 99%
“…The MELD score is a prospectively developed and validated scale for the severity of end-stage liver disease that uses the quantitative, objective values of serum TBIL, serum creatinine, and INR of prothrombin time to predict patient mortality in patients with advanced liver disease [16,40]. Mao et al’s study reported that the MELD score was related to the prognosis of patients with HBV-related acute-on-chronic liver failure [41]. We found that although the AUC of PAF-AH was lower than the AUC of the MELD score for predicting CSHB, the AUC of PAF-AH combined with MELD score was higher than that of PAF-AH or the MELD score alone.…”
Section: Discussionmentioning
confidence: 99%
“…Nearly 90% of patients experience an improvement in symptoms such as fatigue or abdominal distension following NBAL therapy, and liver function parameters have been shown to improve significantly in all tested subjects (17,18). Additionally, NBAL can serve as a bridge to LT (19,20). NBAL treatment prior to LT improves perioperative conditions, reduces the incidence of post-transplant complications, and reduces early mortality (7).…”
Section: Discussionmentioning
confidence: 99%
“…Replacement of the patients' plasma with its wide range of toxins and mediators by fresh frozen plasma is thought to facilitate liver regeneration and recovery. In each of the three studies summarised [ Table 1], [8][9][10] there was a statistically significant improvement either in survival or in the obtaining of a reduced MELD score prior to LT. I would ask you also to take note of the very recently published study of high volume plasma exchange in acute liver failure (ALF) showing in those not transplanted, significant survival improvement.…”
Section: Editorialmentioning
confidence: 99%